Hybrid frequency-selective rasorber with low-frequency diffusion and high-frequency absorption - Zhou, Lin (2022)
In this article, a novel frequency-selective rasorber (FSR) is proposed, which provides a high-efficiency transmission band and a broadband radar cross section (RCS) reduction by hybridizing low-frequency diffusion and high-frequency absorption. The FSR comprises three layers. A broadband second-order bandpass frequency-selective surface is designed as the bottom layer, which has a reflection-transmission-reflection frequency response, and acts as an equivalent ground plane for the upper layers outside the transmission band. A circuit analog absorber and a coding metasurface are designed as the middle and top layers, respectively. They use absorption and diffusion to reduce the RCS at high- and low-frequency bands. In the coding metasurface, miniaturized and absorptive techniques are utilized to suppress the harmonic resonances. The whole FSR unit cell exhibits a cross-polarized reflection-transmission-absorption frequency response. A co-polarized transmission magnitude larger than -1.5 dB from 7.4 to 12.1 GHz and a co-polarized reflection magnitude less than -10 dB from 3.1 to 20 GHz are observed in the full-wave simulation under the normal incidence. An FSR sample with 20×20 unit cells is designed and measured for verification. The measurement agrees well with the simulation, and it shows a significant monostatic RCS reduction from 3.3 to 20 GHz in comparison with a metallic plane of the same size.